Optimizer Performance Test on CNN Long Short-Term Memory Network for Car Sales Forecasting (Universitas Brawijaya, 2025)
In the automotive industry, forecasting future demand is particularly crucial due to the complexity of production processes and supply chains. This article examines the comparative performance of a hybrid CNN-LSTM model for car sales forecasting, utilizing seven optimization algorithms: Adam, RMSprop, SGD, Adagrad, Adadelta, Adamax, and Nadam. Each optimization method has its own advantages. For instance, Adam offers fast convergence, while RMSprop is more effective in handling large gradient fluctuations. Adagrad is well-suited for managing gradient magnitude variations, whereas Adadelta addresses Adagrad’s limitations. Adamax is ideal for models with a broader parameter space, and Nadam combines Nesterov Accelerated Gradient and Adam, making it suitable for tasks requiring both momentum and adaptive learning. This study demonstrates that the CNN-LSTM model optimized with Nadam delivers the best performance, achieving a Mean Squared Error (MSE) of 35,383.14 and a Root Mean Squared Error (RMSE) of 188.10. In comparison, traditional methods such as ARIMA yield an MSE of 59,105.94 and an RMSE of 243.11. These findings indicate that the CNN-LSTM model optimized with Nadam outperforms conventional time series forecasting methods in predictive accuracy.